Virtual Reality Exposure Therapy: The Digital Frontier in Treating PTSD and Phobias - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The Convergence of Immersion and Healing: VRET in Modern Psychiatry The landscape of mental healthcare is being transformed by the convergence of clinic...
Keywords: Digital Health; Healthcare Innovation; Patient Care; Machine Learning; Medical Ethics